Inclusive Education in the 21st Century: Challenges, Strategies, and Innovations - Marwah, Sopa Siti; Anisah, Ani Siti; Nurzakiah (Indonesian Scientific Publication, 2025)
This study presents a narrative review of inclusive education as a defining priority in 21st-century learning, reflecting global efforts to ensure equitable access for diverse learners. Literature was systematically collected from Scopus, Web of Science, and Google Scholar using keywords such as inclusive education, 21st century learning, digital divide, pedagogical innovation, and equity in education. Inclusion criteria focused on peer-reviewed studies published between 2010 and 2025 addressing inclusivity in formal educational contexts. The findings reveal persistent challenges such as limited resources, technological inequities, inadequate teacher preparedness, and inconsistent policy frameworks. Comparative evidence shows that low-income regions face infrastructural barriers, while wealthier nations often encounter cultural resistance to inclusion. Effective strategies identified include STEAM pedagogy, peer learning, and culturally responsive teaching, which foster collaboration, engagement, and equity. Technological innovations such as artificial intelligence, the Internet of Things, and immersive virtual environments demonstrate significant potential to personalize education and expand accessibility, yet disparities in access to technology remain critical. The discussion highlights the importance of systemic reforms, teacher professional development, and adaptive learning environments in advancing inclusive practices. Future research should explore longitudinal impacts and emphasize marginalized learners’ perspectives. Overall, the review concludes that integrating innovative pedagogy, digital tools, and supportive policy frameworks is essential for building inclusive, equitable, and resilient educational systems in the 21st century.